Access to justice for persons with psychosocial disabilities : a comparative analysis of participation in the Kenyan criminal justice system - Juma, Paul Ochieng (Routledge, 2026)
"Taking Kenya as a case study, this book examines the application of criminal procedure in the context of persons with psychosocial disabilities. It discusses how the right to participation of persons with psychosocial disabilities who have been declared 'unfit' can be best protected during and after the criminal process in Africa and at the international level. In doing so, it hypothesises that the social model of disability is inadequate to respond to violations against the right to participation of persons with psychosocial disabilities in the criminal justice system and thus the need for other normative frameworks such as Foucauldian and decolonial theories. It recommends that legislative enactment and reform are imperative not only to promote participation in access to justice but also to remove the barriers inhibiting the legal capacity of persons with psychosocial disabilities. The study will encourage inter-continental dialogue on disability, unfitness declarations, and participation policy analysis, while also contributing to theory and legal development. The book will be of interest to academics, researchers and policy-makers working in the areas of Criminal Procedure, Disability Studies and International Human Rights Law"-- Provided by publisher.
Keywords: Offenders with mental disabilities -- Legal status, laws, etc. -- Kenya.; Mentally ill offenders -- Services for -- Kenya.; Insanity (Law) -- Kenya.; Mental health laws -- Kenya.; Defense (Criminal procedure) -- Kenya.; Criminal justice, Administration of -- Kenya.; Legal assistance to people with disabilities -- Kenya.; People with disabilities -- Legal status, laws, etc. -- Kenya.; International law and human rights -- Kenya.; elektronické knihy; electronic books